A study on the interaction between two weevils Neochetina eichhorniae and N. bruchi, and the mirid Eccritotarsus catarinensis, as biological control agents of water hyacinth Eichhornia crassipes - Obinna, Ajuonu (My University, 2009)
Water hyacinth Eichhornia crassipes (Martius) Solms-Laubach is an invasive floating aquatic weed pest of South American origin that was distributed around the world primarily because of its attractive purple flowers. Due to its rapid growth, it is an important aquatic weed in tropical and subtropical regions worldwide. In Benin, it affects boat traffic, fishing and domestic use of water by about 200,000 inhabitants in several communities. When it became a serious problem in the late 1980s, the only control option approved by the government of Benin was biological control because it is sustainable and environmentally friendly. This dissertation examined the biological control agents released against the weed. Two studies were conducted on the interaction between arthropod biological control agents, using the mirid Eccritotarsus catarinensis (Carvalho), and two weevils, Neochetina eichhorniae (Warner) and N. bruchi Hustache. The third study, investigated the displacement of E. catarinensis in the laboratory culture by an indigenous mirid Nycticapsus sp. The objective of the first study was to determine the influence of adult weevil feeding scars on the mirid released to complement biological control by the weevil. Result show that adults and nymphs of E. catarinensis had high mortality (3-5 folds) on plants with high levels of old feeding scars by adult N. eichhorniae and N. bruchi. In contrast, mirids survived well on plants with recent adult weevil feeding scars or on undamaged plants. These results indicate that the mirid is compatible with the two weevil species under certain conditions and will therefore contribute to enhanced biological control of the weed. The second study investigated the impact of N. eichhorniae and E. catarinensis separately and in combination on water hyacinth grown in culture with another aquatic plant, water lettuce (Pistia stratiotes), at varying planting densities. Without herbivory by either agent, water hyacinth was 18 times more competitive than water lettuce, as estimated from the fresh weight. Reduction in the production of flowers by herbivory was highest (100%) in the treatment with both species. On free water, where both herbivores can reproduce well, mirids might have a short-term initial effect, but in the longer term, when all water hyacinth plants become infested, the weevil out-competes the mirids completely. In treatment with both species, the combined use of the weevils and the mirids is, however, highly justified essentially in situations where the weevil is not efficient, as on stranded water hyacinth where the weevil pupae cannot survive. Nycticapsus sp was regarded as one of the reasons for the failure of E. catarinensis to establish in Benin. Therefore in the third study, E. catarinensis was reproductively more competitive, producing 816.8 adults compared to 451.1 adults by Nycticapsus in single species treatments and (372.2) compared to (268.0) in combination experiment did not show that Nycticapsus sp. could displace E. catarinensis in a laboratory culture. In conclusion, where the weevils have already established, it will not prevent the establishment of the mirid. Combining the mirid with the weevil will have either an additive effects on water hyacinth populations, or, at worst no effect. The mirid could provide also alternative control at sites where the weevils do not establish because of unfavourable/unsuitable environmental conditions.